Do we access meaning when we name Arabic digits? Electrophysiological evidence. - Macizo, Pedro; Álvarez, Alejandro (British Journal of Psychology, 2018)
In this study, we evaluated whether the naming of Arabic digits required access to semantic information. Participants named pictures and Arabic digits blocked by category or intermixed with exemplars of other categories while behavioural and electrophysiological measures were gathered. Pictures were named slower and Arabic digits faster in the blocked context relative to the mixed context. Around 350–450 ms after the presentation of pictures and Arabic digits, brain waves were more positive in anterior regions and more negative in posterior regions when the blocked context was compared with the mixed context. The pattern of electrophysiological results suggests that pictures and Arabic digits are both processed semantically and they are subject to repetition effects during the naming task.